Modelling the abundance of grey seals (Halichoerus grypus) along the Norwegian coast - Øigård, Tor Arne; Frie, Anne Kirstine; Nilssen, Kjell Tormod; Hammill, Mike Osborne (ICES Journal of Marine Science, 2012)
<qd> Øigård T. A., Frie A. K., Nilssen K. T., and Hammill M. O. Modelling the abundance of grey seals ( Halichoerus grypus ) along the Norwegian coast. – ICES Journal of Marine Science, doi:10.1093/icesjms/fsq103. </qd>An age-structured population dynamics model of the Norwegian grey seal ( Halichoerus grypus ) population has been developed. The model is of a Bayesian character in the sense that priors for various parameters were used. Model runs indicated an increase in the abundance of the total Norwegian grey seal population during the last 30 years, suggesting a total of 8740 (95% confidence interval: 7320–10 170) animals in 2011. A total catch of 707 (95% confidence interval: 532–882) grey seals would maintain the population size at the 2011 level. Model runs suggest that current catch levels will likely result in a reduction in the population size in Sør-Trøndelag and Nord-Trøndelag counties, and an increase in the population size in Rogaland, Nordland, Troms, and Finnmark counties. The model runs assumed that 80% of the seals taken in Rogaland came from the UK and that 50 and 55% of the catches in Troms and Finnmark, respectively, were immigrants from Russia.